2019
DOI: 10.1002/ange.201913309
|View full text |Cite
|
Sign up to set email alerts
|

Single Chromium Atoms Supported on Titanium Dioxide Nanoparticles for Synergic Catalytic Methane Conversion under Mild Conditions

Abstract: Direct conversion of methane to value‐added chemicals with high selectivity under mild conditions remains a great challenge in catalysis. Now, single chromium atoms supported on titanium dioxide nanoparticles are reported as an efficient heterogeneous catalyst for direct methane oxidation to C1 oxygenated products with H2O2 as oxidant under mild conditions. The highest yield for C1 oxygenated products can be reached as 57.9 mol molCr−1 with selectivity of around 93 % at 50 °C for 20 h, which is significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Further oxidation of CH3OH can lead to HCHO, HCOOH, and CO2. 47,48 Here, when CH3OH was directly used as the reactant instead of CH4 (Figure 4b), formation of a small amount of HCHO and CO2 was confirmed by 1 H NMR and GC-TCD analysis, respectively. Combined, CH3OOH is a key intermediate in the reaction, which formed via CH4 oxidation and is then converted into CH3OH, HCHO, HCOOH, and CO2.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 83%
See 3 more Smart Citations
“…Further oxidation of CH3OH can lead to HCHO, HCOOH, and CO2. 47,48 Here, when CH3OH was directly used as the reactant instead of CH4 (Figure 4b), formation of a small amount of HCHO and CO2 was confirmed by 1 H NMR and GC-TCD analysis, respectively. Combined, CH3OOH is a key intermediate in the reaction, which formed via CH4 oxidation and is then converted into CH3OH, HCHO, HCOOH, and CO2.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 83%
“…Increasing H2O2 amount from 400 to 4000 μmol led to a remarkable, monotonous decrease both in oxygenated products (from 7 to 1.2 μmol) and in methanol selectivity (from 92% to 42%). According to the literature, 16,48 H2O2 undergoes splitting supplying •OH radicals, and the activation of CH4 occurred via a radical mechanism. It was reported that excessive H2O2 leads to termination of the reaction and thus reduces the product formation.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct conversion of methane to high value-added chemicals (e.g., methanol, ethanol, formic acid, and other oxygenates) is of great significance for the efficient utilization of methane resources due to the abundant reserves of natural gas in shale gas and combustible ice. Nowadays, the traditional methane conversion mainly employs the indirect oxidation process with high temperature and pressure through methane reforming and Fischer–Tropsch synthesis, belonging to the expensive and energy-intensive industries. On the contrary, the direct methane conversion under mild temperature and pressure is more efficient and promising, which serves as the “grail reaction” in the C1 chemical industry. However, direct methane conversion has some insurmountable challenges leading to low product selectivity and reaction efficiency. ,, One is ascribed to the stable four C–H bonds (Δ H C–H = 104 kcal mol –1 ) and low polarizability in methane molecule, which is difficult for methane molecule to be activated. Another is that the oxidation products are more susceptible to be further oxidized to CO 2 compared with methane, resulting in the uncontrolled oxidation process. ,, Therefore, it is essential to develop highly efficient catalysts for direct methane conversion, but this remains challenging.…”
Section: Introductionmentioning
confidence: 99%